2022
DOI: 10.3354/meps13964
|View full text |Cite
|
Sign up to set email alerts
|

Investigating avoidance and attraction responses in lesser black-backed gulls Larus fuscus to offshore wind farms

Abstract: Movements through or use of offshore wind farms by seabirds while commuting or foraging may increase the potential for collision with turbine blades. Collision risk models provide a method for estimating potential impacts of wind farms on seabird populations, but are sensitive to input parameters, including avoidance rates (ARs). Refining understanding of avoidance through the use of high-resolution empirical movement data has the potential to inform assessments of the collision impacts of offshore wind farms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…10 km (Mendel et al, 2019;Vilela et al, 2021;Garthe et al, 2023), while other species, such as large gulls (Larus sp. ), appear to show either no response or attraction to turbines (Welcker and Nehls, 2016;Johnston et al, 2022) and cormorants (Phalacrocorax carbo) are regularly reported to be attracted to turbines, or more pertinently to the structures and the opportunities for roosting provided (Canning et al, 2013;Leopold et al, 2013). Contrary to the results of this study, guillemot and razorbill have most often been reported to show intermediate levels of displacement/avoidance (e.g.…”
Section: Displacement Rates Found At Other Owfscontrasting
confidence: 67%
“…10 km (Mendel et al, 2019;Vilela et al, 2021;Garthe et al, 2023), while other species, such as large gulls (Larus sp. ), appear to show either no response or attraction to turbines (Welcker and Nehls, 2016;Johnston et al, 2022) and cormorants (Phalacrocorax carbo) are regularly reported to be attracted to turbines, or more pertinently to the structures and the opportunities for roosting provided (Canning et al, 2013;Leopold et al, 2013). Contrary to the results of this study, guillemot and razorbill have most often been reported to show intermediate levels of displacement/avoidance (e.g.…”
Section: Displacement Rates Found At Other Owfscontrasting
confidence: 67%
“…There has been very limited empirical validation of CRMs, and terrestrial studies of raptors in Spain found low correlation between actual collisions and predicted collision risk from CRMs (De Lucas et al, 2008). The models are particularly sensitive to avoidance rates; avoidance can occur at multiple spatial and temporal scales and is difficult to measure quantitatively, though advances in technology, such as GPS and the abovementioned combined radar/camera systems, are providing new insights (Johnston et al, 2022;Tjørnløv et al, 2023). Recognizing the potential variation in many CRM input parameters, there have been efforts to develop stochastic models to better reflect uncertainty and incorporate spatiotemporal variation (McGregor et al, 2018).…”
Section: Current Knowledgementioning
confidence: 99%
“…Turbine blades are a potential collision risk to seabirds; estimating the number of collision mortalities that might result from the development of a wind farm is an important aspect of Environmental Impact Assessments (EIAs). The extent of collision risk posed by wind farms to seabirds is dependent on several factors including: the flight heights exhibited by birds in relation to the rotor swept area of a turbine [ 3 ]; their flight speeds [ 4 ]; and avoidance behaviour undertaken in relation to individual turbines [ 5 , 6 ], or entire wind farms [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tracking data have also shown how birds adjust their flight heights in response to turbine rotor swept areas [ 5 , 25 ]. Therefore, bird-borne telemetry can be routinely applied to examine: seabird area use in the offshore wind farm consenting process; responses to offshore wind farms following consent and construction [ 7 , 26 ]; and detect direct interactions with turbines [ 5 , 9 ]. The impacts of collision on seabird populations arising from offshore wind farms are usually assessed in EIAs through Collision Risk Models (CRMs) such as the Band model, a mechanistic model which estimates the number of collisions with a wind farm based on the likelihood of a bird colliding with a turbine blade while flying through the rotor swept zone (RSZ), and the number of birds potentially occupying the RSZ at any given time within the wind farm [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%